2020
DOI: 10.1007/s00300-020-02746-8
|View full text |Cite
|
Sign up to set email alerts
|

High Arctic biocrusts: characterization of the exopolysaccharidic matrix

Abstract: Biocrusts can be found in a wide array of habitats, where they provide important ecosystem services. These microbial associations are particularly important in High Arctic environments, where biocrust colonize the newly exposed barren soil after glacier retreat and significantly contribute to soil stabilization and nutrient cycling. Starting from incipient, structurally simple biolayers, they develop in complexity, increasing from the glacier terminus. Starting from a simple community structure, mainly constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…A similar trend of biomass and nutrients accumulation within the crust surface rather than in the bare soil was observed along an elevation gradient from 5300 to 5900 m asl in the Tibetan plateau (Chu et al, 2016;Janatkov a et al, 2013). NMR analysis of BSCs revealed the load of O-alkyl, alkyl and N-alkyl carbon, indicating that the input of carbon derived from the biocrust comprises polysaccharides and aliphatic biopolymers, in agreement with the BSC-produced extracellular polymeric substances (Mugnai et al, 2020;Rossi et al, 2018). Carbon transfer from the biocrusts to the substrate below was mainly observed in temperate conditions for well-developed BSC like those moss-dominated (Dümig et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…A similar trend of biomass and nutrients accumulation within the crust surface rather than in the bare soil was observed along an elevation gradient from 5300 to 5900 m asl in the Tibetan plateau (Chu et al, 2016;Janatkov a et al, 2013). NMR analysis of BSCs revealed the load of O-alkyl, alkyl and N-alkyl carbon, indicating that the input of carbon derived from the biocrust comprises polysaccharides and aliphatic biopolymers, in agreement with the BSC-produced extracellular polymeric substances (Mugnai et al, 2020;Rossi et al, 2018). Carbon transfer from the biocrusts to the substrate below was mainly observed in temperate conditions for well-developed BSC like those moss-dominated (Dümig et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…Thus for instance, while sulfated groups and uronic acids are hydrophilic (Rossi and De Philippis, 2016), their presence cannot fully explain water absorption by the crust. For example, while young cyanobacterial crusts were found to only posses low amounts of uronic acids (Mugnai et al, 2020b), young cyanobacterial crusts were still observed to readily absorb water during a sprinkling experiment, and subsequently to generate runoff (Kidron, 2015). Nevertheless, it is believed that water absorbance may vary in accordance with the EPS properties (Chenu, 1993).…”
Section: Synthesismentioning
confidence: 99%